New combinations and synonymies in the weevil genus Lyterius Schönherr (Coleoptera, Curculionidae), with a conspectus of historical works on Daldorff’s Sumatran beetles - Prena, Jens; Hsiao, Yun; Oberprieler, Rolf G. (Zootaxa, 2023)
In preparation for a future taxonomic revision, we explore provenance, collectors, original owners and current repositories of the type material for three available genus-group names, Lyterius Schönherr, 1844, Barisoma Motschulsky, 1863 and Plaxes Pascoe, 1885, which have been applied to a group of small, relatively flat weevils associated with Pandanaceae. Lectotypes are designated for Rhynchaenus musculus Fabricius, 1802 and Plaxes impar Pascoe, 1885. The lectotype of Rh. musculus is designated as neotype for Curculio abdominalis Weber, 1801, making the species names objective synonyms (reestablished synonymy), with C. abdominalis having date priority. The names Barisoma Motschulsky and Plaxes are placed in synonymy with Lyterius (new synonymies). Five valid species names are recognised in Lyterius, L. abdominalis (Weber), L. dispar (Faust, 1896) new combination, L. impar (Pascoe) new combination, L. instabilis Boheman, 1844 and L. pandanicola (Motschulsky, 1863) new combination. We also provide an overview of the early descriptive works on Sumatran beetles collected by Daldorff and their original owners.